Clustering of Mathematical Skill Improvement for Children with Special Needs Using K-Means Clsutering: A Case Study at Mutiara Al Islam Therapy Surakarta - REMAWATI, DWI; Sandradewi, Kumaratih; Irawati, Tri; Fitriasih, Sri Hariyati (Ittishal Educational Research Journal, 2024)
The ability to understand mathematics in children with special needs (CSN) needs to be constantly improved. Because the capabilities of CSNs are not the same, they should be grouped based on the results of the evaluations that have been carried out. The purpose of this study is to group children with special needs who receive therapy at Mutiara Al Islam Therapy based on the progress of their mathematical skills. For grouping, use the K-Means Algorithm because this method can be effective in grouping data. Data was obtained from the Mutiara Al Islam therapy institution in Surakarta. The data is in the form of initial math skill scores and new math skill scores, the next process is calculated as a percentage increase in intentions, then clustered. The result of this study is the formation of 2 clusters, namely low improvment and high improvment, so that it can help therapists to improve CSN math skills based on the results of the cluster. Based on the results of the silhouette validity test, the accuracy level of cluster 1 is 0.575629 and cluster 2 is 0.471283.